ESTIMATION OF THE MASS AND THE SPECIFIC MOMENTOF ROTATION OF A BLACK HOLE IN THE CENTER OF SPHERICAL CLUSTER M15 - Kisselev, A. A.; Gnedin, Yu. N.; Shakht, N. A.; Grosheva, E. A.; Piotrovich, M. Yu.; Natsvlishvili, T. M. (Одеські астрономічні публікації, 2008)
Using dispersions of radial velocities of stars, being near to the center of spherical cluster M15, and having applied integral of energy, we have estimated the minimal mass of the central body as 2 x 103 masses of the Sun. The estimation of kinetic energy of outflow of substance of the area surrounding a black hole in M15 also is fulfilled, and the size of the specific angular moment of rotation of a black hole a/MBH is determined.